Crosstalk of autophagy and ferroptosis in cardiovascular diseases: from pathophysiology to novel therapy - Changhao Hu; Siying Gao; Xinyi Li; Kaiqing Yang; Ye Cheng; Wei Guo; Huijun Wu; Xueqin Cheng; Weiwen Zhao; Yuxuan Kong; Haoyuan Hu; Songyun Wang (Redox Biology)
Cardiovascular diseases (CVDs) are characterized by high morbidity and mortality rates, imposing substantial epidemiological and economic burdens worldwide. Among the multifaceted mechanisms implicated in CVDs, autophagy and ferroptosis, two intimately linked cellular processes, emerge as pivotal pathophysiological contributors. Autophagy, as an evolutionary conserved process that mediates the degradation and recycling of intracellular components, including proteins and organelles, exerts critical regulatory effects on iron metabolism and lipid homeostasis through various specialized forms, including ferritinophagy and lipophagy. Conversely, ferroptosis, an iron dependent form of cell death, involves oxidative stress and the accumulation of lipid peroxides, often triggered by iron overload and the dysfunction of glutathione peroxidase 4 (GPX4). The intricate crosstalk between these two processes, particularly ferritinophagy-mediated iron regulation influencing ferroptosis, plays a crucial role in diverse CVDs contexts. Key regulatory molecules, such as Beclin-1 and nuclear factor E2-related factor 2 (Nrf2), function as central hubs, orchestrating the intricate interplay between autophagy and ferroptosis. Through a comprehensive examination of these mechanisms across various CVDs pathologies, we summarize the latest findings and outline potential therapeutic strategies targeting the crosstalk between autophagy and ferroptosis. As the inaugural review focusing on autophagy-ferroptosis interactions in CVDs, this work significantly enriches our understanding of the pathophysiology of CVDs and identifies novel therapeutic targets with potential for precision medicine interventions in managing CVDs.